THE IMPACT OF NATURAL PRODUCTS EXTRACTS ON ORTHODONTIC TEETH MOVEMENT: AN EXPERIMENTAL IN VIVO STUDY - ABBOOD, AHMED KAMAL; AL-SULTAN, MUSTAFA MUATH HAMED (Journal of Duhok University, 2023)
Background: The use of natural products in the field of dental health and improving oral hygiene is well established in multiple previous studies. However, their use in orthodontics and especially  their impacts on  teeth movements have not been previously described. Among the wide range of natural products spread in many parts of the world and the increased interest in them in recent years are green tea, pomegranate  extracts and virgin coconut oil.  Aims: This experimental study aimed to estimate the impact of green tea extract, pomegranate extract and virgin coconut oil on orthodontic teeth movement.Methods: An experimental in vivo study design was adopted to conduct this study. Forty rabbits were selected for the experiments. Inclusion criteria were rabbits to be of good health, without dental abnormalities, weight of 1.7-2 kilogram (average adult rabbit weight), aged 7-10 months. Exclusion criteria were rabbits outside the aforementioned parameters, and those who have dental abnormalities. Four groups were assigned with 10 rabbits in each. One group was control, and other three groups were green tea, virgin coconut oil, and pomegranate. Selected rabbits underwent orthodontic experiment , and  the study groups started feeding on these three natural products. After three weeks study period, distance obtained from tooth movement and serum calcium and phosphorus were measured. Results: Statistical analysis comparing the means of these studied groups revealed a statistically significant differences in the orthodontic teeth distance obtained by the coconut oil group versus the other studied groups (p = 0.03).  Additionally, A student t-test analysis to compare means of serum calcium and phosphorus levels showed no statistically significant differences between the mean differences in serum calcium levels (p = 0.84) and mean serum phosphorus levels (p = 0.56).Conclusion: Rabbits received virgin coconut oil feeding protocol obtained higher mean orthodontic teeth movement distance compared to control, green tea, and pomegranate groups